Interpreting Philosophy. The Elements of Philosophical Hermeneutics - Rescher, Nicholas (Philosophische Analyse / Philosophical Analysis, 2007)
Metaphilosophy is philosophy's poor and neglected cousin. Philosophers are on the whole too busy doing philosophy to take time to stand back and consider reflectively how the project itself actually works. And they lead tend to produce texts without too much consideration of how this looks from the standpoint of the consumer. All this, it seems to be, affords good reason for attending to philosophical hermeneutics, reflecting on the issue of how philosophical texts are to be understood and interpreted.